Mathematical Modeling of Glucose Regulation System in Term of Perturbed Coefficients - Basil, Mustaffa Mohammed; Masood, Farah Mohammed Ridha (Al-Khwarizmi Engineering Journal, 2017)
In this research a recent developed practical modeling technique is applied for the glucose regulation system identification. By using this technique a set of mathematical models is obtained instead of single one to compensate for the  loss of information caused by the optimization technique in curve fitting algorithms, the diversity of members inside the single set is interpreted in term of restricted range of its parameters, also a diagnosis criteria is developed for detecting any disorder in the glucose regulation system by investigating the influence of variation of the parameters on the response of the system, this technique is applied in this research practically  for 20 cases with association of  National Center for Diabetes / Al Mustanseryia University.